Pengenalpastian Faktor Psikologi yang Menentukan Penglibatan Pelajar Universiti Awam Tempatan dalam Aktiviti Fizikal Masa Senggang (Jurnal Pembangunan Sosial, 2015)
The purpose of this study is to identify the infuence of attitude, self-effcacy, and motivation on leisure time physical activity and sport participation among students in the Malaysia public universities. The study sample comprised of 551 male and 801 female undergraduates who were selected by means of random cluster sampling. Questionnaires were utilized to collect data. The results of the study showed that there were positive correlations among leisure attitude, motivation, self-effcacy and leisure time physical activity and sport participation among undergraduate students. The results also revealed that motivation and self-effcacy were the best predictors of leisure time physical activity and sport participation. This study suggests that in the effort to encourage the student’s leisure time physical activity and sport participation and involvement, the university management should plan and organize programmes to develop positive attitude among students, increase their self- effcacy and motivation level of physical activity and sport participation.